Mesocosmic study on autogenous shrinkage of concrete with consideration of effects of temperature and humidity - Yan Hai (Water Science and Engineering, 2009)
A study on the autogenous shrinkage (AS) of concrete from a mesocosmic perspective was carried out using numerical simulation technology. The temperature history and the autogenous relative humidity (ARH), two factors that have been shown to have occasional influence on this process in previous studies, were introduced into this study. According to these concepts, a program for simulation of the temperature field, humidity field, and stress field based on the equivalent age method and a fully automatic aggregate modeling tool were used. With the help of these programs, the study of a small concrete specimen provided some useful conclusions: the aggregate and the matrix show distinct distribution properties in the temperature field, humidity field, and stress field; the aggregate-matrix interface has a high possibility of becoming the location of the initial cracking caused by AS of concrete; the distribution of random aggregates is extremely important for mesoscopical analysis; and the temperature history is the main factor affecting the AS of concrete. On the whole, inherent mechanisms and cracking mechanisms of AS of concrete can be explained more reasonably and realistically only by considering the different characteristics of material phases and the effects of temperature and humidity.